THE USE OF GRAMMAR TRANSLATION METHOD IN ENGLISH LEARNING TO THE SUB-DISTRICTS’ JUNIOR HIGH SCHOOLS IN TABANAN REGENCY - Sukraningsih, Gusti Ayu Gede; Karmini, Ni Nyoman (IKIP SARASWATI TABANAN, 2023)
Grammar Translation Method is regarded as the old method that still used particularly at the school in sub-districts area. This research purposed to describe the use of Grammar Translation Method in English learning to the sub-districts junior high schools in Tabanan regency. The subjects of this research were three English teachers and 124 students. The data collection techniques used in this research were observation, interview, and documentation. Qualitative data analysis was applied to analyze the data. In accordance with data analysis, it was obtained that (1) Grammar Translation Method (GTM) was used in learning process includes the phases of observing, questioning, collecting data, associating, communicating, (2) Grammar Translation Method was used to increase students’ knowledge and skills in reading and writing. (3) The difficulties faced by the students were utilizing the appropriate vocabulary and structuring sentences. The conclusion of this research is the use of Grammar Translation Method is still required to increase students’ capability and skills, especially in reading and writing.